Guidelines and general information of the Integral Health Journal of the University of El Salvador - Editorial, Comité (Salud Integral, 2023)
Focus and scope Revista Salud Integral of the University of El Salvador (UES) is managed by the Master’s Program of the School of Medicine. The journal is available to the scientific community, academia and clinical decision makers, managers and students in the health sciences. from the University of El Salvador and other national and foreign institutions, as well as professionals from other disciplines, both nationally. Manuscripts are accepted in the field of health sciences, public health, epidemiology, environmental health, social medicine and medical, dental and other specialties in the field of health. It is also available to researchers from UES and other national and foreign institutions who wish to publish original and unpublished scientific articles in the area of health sciences and related branches; it is free and open access to readers. Articles are submitted to double-blind peer review. A researcher selected by the Editorial Board or by the Editor-in-Chief will be invited to write the editorial page. Salud Integral de la Universidad de El Salvador (UES) is managed by the Masters Program of the School of Medicine. The journal is available to researchers from UES and other national or foreign institutions who wish to publish original and unpublished scientific articles in the area of health sciences and related branches; it is free and open access to readers.